FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN CLEANSING BALM EKSTRAK ETANOL BUNGA TELANG (Clitoria ternatea L.) - Farhamzah, Farhamzah; Warsito, Ainun Mar’atus Putri; Yuniarsih, Nia (Jurnal Buana Farma, 2024)
Skin is the outermost layer of the human body that protects the organs inside and skin is the layer that adapts most to the external environment, weather or climate. Facial cleansing is the first step to remove dead skin cells, dirt, sebum and cosmetic residue, which causes acne, redness, irritation and can be made worse by the presence of free radicals. Compounds that are able to ward off free radicals are antioxidants, so this research will make Cleansing Balm with butterfly pea flower extract (Clitoria ternatea L.) as an antioxidant and find out the best formula and storage stability from experimental research by testing antioxidant activity using the DPPH method. The Cleansing Balm preparation was made with three additional concentrations of butterfly pea flower extract (Clitoria ternatea L.), namely F1 (0.1%), F2 (0.2%), and F3 (0.3%). In this research, the results showed that telang flower extract contains alkaloids, flavonoids, quinones, tannins and saponins. The antioxidant activity of Cleansing Balm of butterfly pea flower (Clitoria ternatea L.) shows an IC50 F1 of 95,732 ppm, F2 of 51,368 ppm, F3 of 10,213 ppm. From the research, it can be concluded that Cleansing Balm Formula 3 which contains 0.3% butterfly pea flower extract (Clitoria ternatea L.) is the most effective formula for antioxidant activity